Optical particle measurements reveal cross-shelf turbidity gradients on the Agulhas Bank. (June 2022) - Giering, Sarah L.C.; Noyon, Margaux; Godfrey, Brian; Poulton, Alex J.; Carvalho, Filipa; Roberts, Mike
Abstract: The Agulhas Bank is a moderately productive and dynamic shelf ecosystem. In this region, underwater visibility can, at times, be poor owing to high turbidity near the seabed. However, it is currently unclear what causes high-turbidity events and how far they extend. Using an analysis of optical particle data (backscatter and fluorescence), we show a strong cross-shelf gradient of near-bottom turbidity and distinct particle dynamics across the study region. The region near Port Alfred was characterized by high levels of new production and vertical transport of organic matter to depth via sinking particles. On the Central Agulhas Bank, our observations were consistent with the suggestion of particle retention owing to a larger cyclonic recirculation pattern. Close to the coast we observed four sites with benthic nepheloid layers (BNL) that were likely formed because of resuspension of sediments. Our data indicate that there was no instantaneous link between BNL and sinking phytodetritus, though a time lag between export events and benthic remineralization could have obscured a direct link between surface productivity and BNL formation.